Surface modification of basalt fiber (BF) for improving compatibilities between BF and poly lactic acid (PLA) matrix. Issue 4 (3rd April 2019) - Liu, Shuqiang; Wu, Gaihong; Yu, Juanjuan; Chen, Xiaogang; Guo, Jinhui; Zhang, Xiaofang; Wang, Peng; Yin, Xiaolong
ABSTRACT: Basalt fiber (BF) possesses some excellent properties in temperature resistance, chemical stability, sound absorption and so on. It has been applied to create composites with the polylactic acid (PLA) resin, which could be used as medical equipments, bone repairing materials, automobile shells and others. However, the compatibilities between BF and PLA are understood to be poor. In order to solve the problem, BF was treated by sodium hydroxide solution (NaOH) and then by coupling agent KH550, and the optimal concentration of NaOH was found to be 15 g/L, and the optimal KH550 dosage was 2%. The research revealed that one end of KH550 molecule was reacted with the hydroxyl groups on the surface of BF to form chemical link, and the amino group at the other end of KH550 molecule was reacted with the terminal hydroxyl group or the terminal carboxyl group of PLA molecule to form chemical link. Graphical Abstract: